2014
DOI: 10.1089/g4h.2013.0071
|View full text |Cite
|
Sign up to set email alerts
|

“Fair Play”: A Videogame Designed to Address Implicit Race Bias Through Active Perspective Taking

Abstract: Objective: Having diverse faculty in academic health centers will help diversify the healthcare workforce and reduce health disparities. Implicit race bias is one factor that contributes to the underrepresentation of Black faculty. We designed the videogame ''Fair Play'' in which players assume the role of a Black graduate student named Jamal Davis. As Jamal, players experience subtle race bias while completing ''quests'' to obtain a science degree. We hypothesized that participants randomly assigned to play t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 64 publications
2
49
2
Order By: Relevance
“…"), distrust (e.g., "I think those labels are just excuses"), prejudice (e.g., "I won't associate with crazies like her"), minimization (e.g., "it's a waste of time and energy to consider those things"), illegitimacy (e.g., "psychology isn't a real science like chemistry or physics"), disbelief (e.g., "they just act that way for attention"), antipathy/apathy (e.g., "they need to pull it together, they've got it no harder than everyone else") and possibly even fear (e.g., "that neighbor seems disturbed, maybe he's dangerous"). For many laypeople, these and other similar results from active perspective-taking and exposure [2].…”
Section: Myth #1: Mental Disorders Are Unimportantsupporting
confidence: 73%
“…"), distrust (e.g., "I think those labels are just excuses"), prejudice (e.g., "I won't associate with crazies like her"), minimization (e.g., "it's a waste of time and energy to consider those things"), illegitimacy (e.g., "psychology isn't a real science like chemistry or physics"), disbelief (e.g., "they just act that way for attention"), antipathy/apathy (e.g., "they need to pull it together, they've got it no harder than everyone else") and possibly even fear (e.g., "that neighbor seems disturbed, maybe he's dangerous"). For many laypeople, these and other similar results from active perspective-taking and exposure [2].…”
Section: Myth #1: Mental Disorders Are Unimportantsupporting
confidence: 73%
“…In addition, Marini, Rubichi, and Sartori (2012) found that imagining one's self being helped by an outgroup improved participant's attitudes towards that out-group whereas imaging another person being helped did not. Another recent study demonstrated that actively taking the perspective of a black character who experienced racial bias in a computer game led to a greater reduction in implicit racial bias than merely reading the about the same experience through text did (Gutierrez et al, 2014). It should be noted, however, that Lai et al (2014) found no evidence that perspective taking of an out-group member led to reduced bias towards that out-group.…”
Section: Perspective Takingmentioning
confidence: 97%
“…This fact may be explained by the fact that in their study the method of perspective taking used was relatively basic consisting of simply seeing a person's face and a short sentence about them. In contrast, the more successful instances of perspective taking tend to involve more immersive techniques such as writing a short essay from the other's perspective (Galinsky & Ku, 2004;Todd & Burgmer, 2013), writing their views about a film clip featuring an out-group member (Shih et al, 2009) or taking the role of an out-group member in a computer game (Gutierrez et al, 2014).…”
Section: Perspective Takingmentioning
confidence: 99%
“…Although strong effects of persuasive games have been found in some studies (Kampf & Cuhadar, 2014;Peng et al, 2010;Ruggiero, 2015), weaker effects have been found in other studies (Barthel, 2013;Gutierrez et al, 2014;Jacobs, 2016;Soekarjo & Van Oostendorp, 2015). Ultimately, however, there are too few empirical studies to derive conclusions on the genre as a whole.…”
Section: Interactivity and Construal Levelmentioning
confidence: 99%